The Effect of Project-Based Learning Model on Creativity of Students in Class XI Religion MAN 1 Polewali Mandar - Mashita; Darwis; Naomi Sahupala, Okky (JURNAL SINTAK, 2025)
This study aims to determine the level of use of project-based learning models of students in class XI Religion MAN 1 Polewali Mandar, to determine the creativity of students in class XI Religion MAN 1 Polewali Mandar, and to determine whether there is an effect of project-based learning models on the creativity of students in class XI Religion MAN 1 Polewali Mandar. This research was conducted at MAN 1 Polewali Mandar using quantitative research. The results showed that there was an influence between the Project-Based Learning Model on the Creativity Level of Students in class XI Religion MAN 1 Polewali Mandar. From the analysis obtained the coefficient of determination (R Square) of 0.406, which means that the effect of the independent variable on the dependent variable is 40.6% and as much as 59.4% is influenced by other factors not included in this study.